Strategic modelling of passenger transport in waterways: the case of the Magdalena River - Berrio, Laura; Cantillo, Víctor; Arellana, Julian (Transport, 2019)
In some Colombian regions, inland waterways play a relevant role in passenger mobility. However, many characteristics of their operation, required for planning purposes, are unknown. Existing data and studies are few and undetailed. In this context, collecting data and developing supply and demand models will make it possible to not only improving the knowledge of inland waterway transport in the country, but also the planning of the system. In this investigation, a survey instrument was designed and employed to collect data about passenger flows in seven ports on the Magdalena River, the most important river in Colombia. The collected information was used to specify and estimate strategic supply and demand models. Models based on the classic four-step model and alternative synthetic models were estimated and compared. The proposed models contribute to better understanding of the behaviour of inland waterway transport passengers. They were used to evaluate policies aimed at improving the users’ level of service and to encourage the utilisation of this mode of transport. Results show that accessibility variables and variables related to zone size define trip generation and distribution. In addition, it was found that inland waterway users in Colombia are highly cost sensitive.